Accountability interactions: multiple accountabilities in the Murray-Darling basin plan - Foster-Thorpe, F (2014)
This thesis investigates whether different public accountability forums interact with one another when they oversee the same decision maker. It contributes to the larger study of how decision makers are held to account in constitutional democracies where the simultaneous operation of multiple accountability relationships has become routine. Looking beyond the dominant assumption that multiple forums autonomously assess a decision maker's accountability against different and diverging standards, I aim to understand whether forums can influence the standards against which other forums evaluate the same decision maker. I draw on political and normative understandings of public accountability to answer one central question: do different public accountability forums interact with one another in a way that influences the scope of what a decision maker is obliged to account for and the normative standards against which that account is evaluated? Answering this research question involves examining the mechanisms by which interactions might occur and the motivations of actors to interact. I begin by critically reviewing the literature on multiple accountabilities, arguing that existing approaches can only partially explain how public accountability is constructed in multiple accountability regimes. I argue the focus on typologies of accountability emphasise the attributes of individual forums and overlook the broader dynamics of the accountability regime. I then develop an analytical framework to examine how the interactions between different forums, and other actors, might reshape the accountability dialogue. This framework is used to analyse the case of the Murray-Darling Basin Plan in Australia (2008-2012). By presenting a contextSrich analysis of interactions between forums, and other actors, I find that multiple forums act in concert with one another and other actors to contest and then reshape the standards against which the two decision makers are evaluated. The thesis concludes by discussing the implications of recognising accountability interactions for understanding multiple accountability regimes.